Increased lateral femoral condyle ratio measured by MRI is associated with higher risk of solitary meniscus injury - Yang, Lei; Xing, Shuxing (Frontiers in Bioengineering and Biotechnology, 2024)
Background Past studies found that an increased lateral femoral condyle ratio is associated with ACL injuries, but it is not clear if there is a link between MRI-measured lateral femoral condyle ratios and meniscal injuries. MRI provides a more accurate selection of measurement planes. Compared to X-rays, it further reduces data errors due to non-standard positions.Objective To study the relationship between knee bone morphology and Solitary meniscal injuries by MRI.Methods A total of 175 patients were included in this retrospective case-control study, including 54 cases of pure medial meniscus injury, 44 cases of pure lateral meniscus injury as the experimental group, and 77 control subjects. MRI images were used to measure the femoral notch width, femoral condylar width, femoral notch width index, lateral femoral condylar ratio (LFCR), posterior tibial slope (PTS), medial tibial plateau depth, and meniscus slope. In addition, carefully check for the presence of specific signs such as bone contusions and meniscal extrusions. Comparing the anatomical differences in multiple bone morphologies between the two groups, a stepwise forward multifactorial logistic analysis was used to identify the risk factors for Solitary meniscal injuries. Finally, ROC curves were used to determine the critical values and best predictors of risk factors.Results MTS, LTS, and LFCR ended up as independent risk factors for meniscus injury. Among all risk factors, LFCR had the largest AUC of 0.781 (0.714-0.848) with a threshold of 72.75%. When combined with MTS (>3.63°), diagnostic performance improved with an AUC of 0.833 (0.774-0.892).Steep medial tibial plateau slope, steep lateral tibial plateau slope angle, and deep posterior lateral femoral condyles on MRI are independent risk factors for meniscal injuries. In patients with knee discomfort with the above imaging findings (X-ray, MRI), we should suspect and carefully evaluate the occurrence of meniscal injuries. It not only provides a theoretical basis to understand the mechanism of meniscus injury but also provides theoretical guidance for the prevention of meniscus injury and the development of intervention measures.Level of evidence III.